Analisis Terjadinya Kredit Macet di Bank Mandiri Surabaya : Implikasi Terhadap Laporan Keuangan - Mifta Wardhani Putri; Tantina Haryati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the factors that cause bad credit at Bank Mandiri Surabaya and its impact on the bank's financial statements. Through a qualitative approach, this study evaluates how bad credit affects financial performance and the accounting policies implemented. Data was collected through interviews with bank management, as well as analysis of financial reports in the last five years. The research results show that less stringent credit policy, unstable economic conditions and weaknesses in internal supervision are the main causes of bad credit. Bad loans have a significant impact on financial statements, especially through increasing the allowance for credit losses which reduces net profit and affects financial ratios. This research provides recommendations for improving the credit assessment system, strengthening internal supervision, and increasing training for staff.